Evaluation of potential biocides for control of the earthworm Eukerria saltensis (Oligochaeta: Ocnerodrilidae), a pest of rice in southern Australia. (June 2016) - Stevens, M.M.; Mo, J.; Warren, G.N.; Doran, G.S.
Abstract: The earthworm Eukerria saltensis can cause severe crop establishment problems in aerially sown rice grown on heavy clay soils in southern Australia. Damage occurs indirectly through destabilization of the topsoil, increased water turbidity, and mobilization of soil nutrients into the water column which leads to increased algal growth. We investigated the possibilities for chemical control of E. saltensis using laboratory bioassays and a series of field trials involving either the use of enclosures in flooded crops or soil incorporation of pesticides into rice fields during fallow periods or shortly before flooding. The four most toxic compounds in 7 day soil/water laboratory bioassays were carbofuran, acetamiprid, bendiocarb and lambda-cyhalothrin which provided corrected mortalities of 86–100% at 2 mg a.i. L −1 . Other compounds that showed some level of efficacy (corrected mortality >20% at one or more rates) were imidacloprid, esfenvalerate, thiacloprid, niclosamide and alpha-cypermethrin. Twenty-six of the 38 pesticides evaluated failed to produce mean corrected mortalities >6% at application rates of up to 2 mg a.i. L −1 . Eight trials were conducted in flooded rice crops using small stainless steel enclosures and carbofuran, thiodicarb, niclosamide and bendiocarb at rates of 1 and 2 kg a.i. ha −1 . Trials were assessed 8–14 days after chemical application. None of these treatments produced a statistically significant decrease in Eukerria biomass, although consistent downward trends in response to higher treatment rates were evident in 2 trials (one with carbofuran and one with bendiocarb). Three trials with liquid pesticides watered into fallow rice fields were conducted with carbofuran (0.5, 1.0 and 5.0 kg a.i. ha −1 ) and thiodicarb (0.94 and 1.87 kg a.i. ha −1 ) however only the 5.0 kg a.i. ha −1 carbofuran treatment provided significant ( P  < 0.05) levels of control. Preflood soil applications of liquid carbofuran, thiodicarb and niclosamide (2 kg a.i. ha −1 ), granular carbofuran and granular ethoprophos (0.5–2 kg a.i. ha −1 ) also did not provide statistically significant levels of control, although the 2 kg a.i. ha −1 liquid and granular carbofuran treatments did provide moderate levels of suppression (49–84%). Although further field trials with compounds such as acetamiprid and lambda-cyhalothrin may prove valuable, our results suggest chemical control of E. saltensis may be difficult to achieve with environmentally acceptable pesticides applied at economically viable rates. Cultural approaches such as appropriate crop rotations and landforming to ensure uniformly shallow water should continue to form the basis of Eukerria management programs. Graphical abstract: Highlights: Eukerria saltensis can cause poor rice crop establishment. Carbofuran, acetamiprid, bendiocarb and lambda-cyhalothrin were active in bioassays. Application of chemicals to flooded crops did not provide effective control. Carbofuran watered into fallow ground reduced E. saltensis populations.